Little busters! Season one, Collection 1, Episodes 1-13 [videorecording (DVD)] - Staff, J. C. (Sentai Filmworks, 2013)
When tragedy struck Riki Naoe as a child, he was rescued from grief over his parent's deaths when four other kids recruited him for their group, the Little Busters. Now in high school, Riki and the other Busters are still friends. Though their vision of being heroes for justice may have faded, they'd still do anything for each other, which is why Riki is now on two special missions: to recruit new members for a baseball team, and to solve a mystery concerning the existence of a 'secret world'.